Sosialisasi Tentang Teknik Dasar Permainan Sepak Bola Pada Karang Taruna Desa Guru Agung 1 Kecamatan Kaur Utara - Personi, Megi; Ertanto, Dody; Ferdiansah, Rahmad (Jurnal Dehasen Untuk Negeri, 2025)
This report outlines the community service activities carried out by Universitas Dehasen Bengkulu with the title "Socialization on the Basic Techniques of Football for the Karang Taruna of Desa Guru Agung 1, Kaur Utara District." The objective of this activity was to enhance the understanding and skills of the Karang Taruna members of Desa Guru Agung 1 in playing football, specifically in mastering the basic techniques of football, including dribbling, passing, shooting, and positioning. The activity began with a socialization session on the fundamentals of football, followed by a practical session to improve the participants' skills. The event was attended by 30 Karang Taruna members of various ages, who were very enthusiastic about participating in each of the materials presented. This activity is expected to enhance football skills among the community, especially the youth, with the hope that it will make a positive contribution to developing sports potential in the village. The results of this activity show a significant improvement in the participants' basic football skills. Furthermore, the participants recognized the importance of sports as a means to maintain physical health and foster solidarity and cohesion within the community. Although there were some technical difficulties in providing visual aids, the activity successfully achieved its objectives. Moving forward, similar activities can be carried out sustainably and expanded with more in-depth training on game strategies and further development of football skills. This program also serves as one of the contributions of Universitas Dehasen Bengkulu in improving the quality of sports in the community and strengthening the relationship between the university and the local community.